Reduction of Peri - Procedural Myocardial injury by Loading dose of Atorvastatin during Elective Percutaneous Coronary Intervention - Saha, Chandan Kumar; Hossain, Solaiman; Mannan, Md Abdul; Ullah, Mohammad; Faruque, Md (Cardiovascular Journal, 2015)
Background: The purpose of the study was to find the effect of loading dose of atorvastatin on the reduction of myocardial injury resulting from percutaneous coronary intervention (PCI). Methods: A total 100 consecutive patients were included in this study of which 50 patients were in the group I who were treated with a loading dose of atorvastatin and the rest 50 patients were in the group II who were treated without the loading dose of atorvastatin.The occurrence of myocardial injury was measured by serum cTn-I level in patients undergoing PCI with or without loading dose of atorvastatin. Results: Elevation of cTn-I after PCI reflects peri-procedural myonecrosis and presage adverse outcome. In this study incidence of cTn-I rise following PCI was 86% without atorvastatin pretreatment and 10% with atorvastatin pretreatment.The incidence of myonecrosis is less in atorvastatin pretreated group and the difference was statistically significant. Conclusion: It is concluded that the loading dose of atorvastatin significantly reduce myocardial injury resulting from percutaneous coronary intervention. Cardiovasc. j. 2015; 8(1): 3-7